Anti-museums and collecting as a subjective act - Danckaert, Marie Sophie (2024)
Had you been a bourgeois of some sort, sometime back in the Renaissance, you might have had the exciting opportunity of penetrating the marvellous realm of a curiosity cabinet. Your breathing would have stilled as you found yourself surrounded with eerie beasts, engravings of foreign lands, and natural wonders beyond the imaginable. Perhaps would you have caught a glimpse of a collection of rocks in the form of shells. The owner, aware of your astonishment, would have taken the care of counting you their story, explaining that such pieces were creations of God himself and were left atop mountains after the Great Flood. And you would have stood there in pure awe, as this potent proof of the Divine’s existence subjugated you to the bone. But maybe would you have been more than a simple curious man of high status seeking the thrill of sating your appetite for wonder. If the like of the noble collector who had granted you access to his museae and yourself a naturalist, this encounter would have represented a perfect opportunity for knowledge exchange, debating such grand questions as if whether or not frogs generated spontaneously from dust, or the formation of some precious stone within the bodies of animals. Now, do not get me wrong. The Renaissance period was not one purely consisting in theories that can only appear as ludicrous to our 21st century perception. This was the era of the Copernican revolution, of the commencement of scientific practice, one that saw the rise of encyclopaedic projects of an unprecedented scale. In response to the discovery of the New World, Sixteenth and Seventeenth century naturalists and humanists actively sought to surpass Antic references in the amassing of knowledge, as the collecting of nature and the wonder invariably attached to this activity constituted a stepping stone for this grand endeavour. In the face of overwhelming novelty, those early savants were concerned less with unquestionable truth than with what could be plausible. In that sense, theories of self-generating animals and Galileo’s law of inertia could be taken just as seriously as one another. The curiosity cabinet – which could be declined as Studio, Museae, or Galeria – ancestor to our modern days museums, constituted the physical repositories of knowledge in which the world was to be studied and attempted to be made sense of. From these microcosms designed to embody the whole of the natural world – human productions included – modern museums were eventually born. In the 18th century, political revolutions and religious reformation prompted the apparition of new ways of thinking. The overwhelming aspect of New World novelty had faded, and it was now time for hard sciences and systematic classification to make their apparition. The separation of disciplines occurred as a logical consequence, while the Enlightenment ideal of knowledge encouraged the opening of public museums dedicated to various topics, theoretically accessible to anyone desirous of educating themselves. As Bruno Latour has argued, the methodical separation of nature and culture as well as the perception of nature as a passive object which can be actively manipulated by humans are largely recognised as the starting point of the modern era. This radical change in interpretation of the world caused a radical break in time in the 18th century, one that gave birth to the illusion the modern human, resolutely turned towards progress and reason, was a better man than its ancestors. However, in his essay We Have Never Been Modern, Latour disputes the reality of modernity. According to him, humanity has never been modern for we have never managed to apply modern values in their entirety. By fabricating such binary oppositions as nature/culture and rejecting tradition in aid of progress, the modern agenda has failed to recognise the complexity of the relationship humanity entertains with nature as well as the subtlety of human experience. By shaping sciences as a universal and objective truth, modernism has relegated other types of beliefs as inferior and subjective. Rationality came to been seen as superior to the feelings inevitably attached to human experience while blatantly ignoring that no human enterprise can ever be objective.1 By borrowing from pre-modern institutions and revealing the flaws of modern museums, antimuseums reject modernity and remind us of the fantastic scope of human experience. It is with the aim of both tackling the authoritarian nature of modern institutions and of reinvigorating wonder that anti-museums eventually appeared in the 20th century. But what are anti-museums, how do they oppose traditional ones? What role does the act of collecting play in their construction? How do anti-museums impact their audience? By raising these interrogations, I hope to demonstrate that anti-museums effectively confute the sustained myth that modern museums breed objectivity, and that, by borrowing from pre-modern tradition, these allow for a much needed return to wonder. In order to answer these questions, this thesis will rely on three case studies: the Collection de l’Art Brut (Lausanne, Switzerland), the Museum of Jurassic Technology (Los Angeles), and the Viktor Wynd Museum (London). I have willingly chosen to focus on anti-museums as varied as possible, whether in their content, founder’s profile, or geographic location, in order to better exemplify the uniqueness inherent to this type of institutions. The Collection de l’Art Brut (CAB) is an anti-museum presenting a wide array of artworks exclusively produced by self-taught creators living on the margins of society, mostly as a consequence of having spent years isolated in mental asylums or behind bars. The term Art Brut – “Raw Art” – was first coined by French painter Jean Dubuffet. The artworks it encompasses, which he perceived as radically “anti-cultural” by nature, stood for him as supreme expressions of creativity and the proof that all human beings bear within themselves the potential to be an artist. It is in 1945 that Dubuffet first started gathering this collection. After 30 years of clandestine exhibitions in Parisian basements, it finally found an official home in Lausanne in 1976 at Dubuffet’s request, under the supervision of curator and Art Brut specialist Michel Thévoz. Nested behind a storefront in Culver City, Los Angeles, the Museum of Jurassic Technology (MJT) has many more mysteries to offer than its name. At first glance, all the elements are there to elicit the modern museum. Entering through the gift shop, visitors then find themselves roaming dimly lit galleries, glancing at carefully elaborated dioramas, and reading endless scientific explanations and academic references supporting the authenticity of the displays. Yet, this familiar, almost comforting setting, serves to conceal an adroitly elaborated trick blurring the limits between facts and fiction. Many of the facts exhibited in this museum were indeed born from Wilson’s imagination, but his skillful association of widely known facts and obscure, made up fables is enough to convince most viewers of the legitimacy of the exhibitions. Finally, the Viktor Wynd Museum (VWM) is a small museum located in the Hackney borough in London. The term curiosity cabinet would perhaps stand as a more suitable definition of the VWM for it bears copious similitudes with these, as we shall later discuss. The items themselves, for the most part fantastic, squalid, or even frankly abhorrent in some cases, are reminiscent of a freak show’s sinister sensationalism. A particularly compelling aspect of this museum is that it bases a great deal of its marketing strategy on proclaiming itself as an antimuseum, with a strong emphasis on its disruptive function. Basing its arguments on these three case studies, this thesis will therefore seek to identify the differences between modern museums and anti-museums, their points of convergence, common features, and the potential impacts they might each have on their public and, more widely, society. While there exists an endless variety of museums, public or private, treating of topics as varied as art, ethnology, naval history, death, gas, magic, or even commercial failure, it would be impossible to establish an exhaustive account of their respective peculiarities. For the sake of clarity, I shall thus name museums fitting our modern definition of these institutions modern museums, in order to better distinguish them from anti-museums. The first chapter will therefore start by analyzing the characteristics and interests of the antimuseum, using a comprehensive history and analysis of the modern museum in order to better understand how anti-museums differentiate themselves from these well-established institutions. Over a second chapter, I will move on to exploring the importance and meaning of collecting, its role in the making of modern museums and anti-museums alike, its inevitable subjectivity, and the influence it might exert on both viewers and the collectors themselves. Lastly, the third chapter will focus on public reception, delving into viewers expectations et behaviours in museums as well as to what extent might anti-museums might constitute a deceiving or rejoicing experience for their spectators.